IMPROVEMENT OF 1XK CLEANING TECHNOLOGY IN THE PROCESS OF CLEANING SEED COTTON FROM SMALL IMPURITIES (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article is about the national process of processing raw cotton with a variety of problems in cleaning large and small scum. In order to find solutions to this problem, it has been determined by the analysis of the effectiveness of the small scale cotton-fertilization technology for other cotton fertilizers compared to other models